Architectural Peculiarities of the Jewish Town Block in Kremenets - Panfiłova, Oleksandra (Tokyo University Press, 2017)
The article analyzes typological peculiarities and significance of the lost buildings of the Jewish town block in formation of the historical town image. Numerous meandering streets of the town were thickly covered with buildings, unique wooden dwelling houses. Kremenets was old fashioned town which preserved its image of the end of the XVIIIth and the beginning of the XIX th century. The article deals with the description of the traditional form of settling and the organization of life in the Jewish communities. The peculiarity of the origin and development of wooden architecture in the central part of the town connected with cultural processes in the Volyn region at the end of the XIXth and the beginning of the XXth century is also observed. The article shows the influence of surroundings and sort of activity upon the architecture, main features of structural elements of the shtetl (Jewish town block) which was completely ruined during the German military occupation in July 1942.
Keywords: Kremenets; shtetl; decoration; wooden architecture; structural elements